Corneal nerve fractal dimension: a novel corneal nerve metric for the diagnosis of diabetic sensorimotor polyneuropathy - Chen, Xin; Graham, Jim; Petropoulos, Ioannis N.; Ponirakis, Georgios; Asghar, Omar; Alam, Uazman; Marshall, Andrew; Ferdousi, Maryam; Azmi, Shazli; Efron, Nathan; Malik, Rayaz A. (Association for Research in Vision and Opthalmology, 2018)
Objective: Corneal confocal microscopy (CCM), an in vivo ophthalmic imaging modality, is a noninvasive and objective imaging biomarker for identifying small nerve fiber damage. We have evaluated the diagnostic performance of previously established CCM parameters to a novel automated measure of corneal nerve complexity called the corneal nerve fiber fractal dimension (ACNFrD).